Elucidating the performance of (N-(3-aminopropyl)-1, 3-propanediamine) activated (1- dimethylamino-2-propanol) as a novel amine formulation for post combustion carbon dioxide capture. (1st October 2020) - Dey, Anirban; Dash, Sukanta Kumar; Mandal, Bishnupada
Highlights: Equilibrium CO2 solubility into novel amine blends were experimentally measured. Modified KE and FFNN models used to correlate the CO2 solubility in amine blends. Solvent speciation profile, pH as well as Heat of absorption were estimated. 13 C NMR and FTIR-ATR analysis were performed to assess the reaction scheme. Thermophysical properties were measured and correlated using R-K and G-N models. Abstract: The exploration of energy-efficient amine solvents for CO2 removal from flue gas streams has been adopted as a key strategy for the wide implementation of CO2 capture technology in fossil fuel-based power plants for post-combustion CO2 capture. The current study entails an insight into the CO2 absorption performance of a novel aqueous amine blend of N-(3-aminopropyl)-1, 3-propanediamine (APDA) and 1-dimethylamino-2-propanol (1DMAP) with special emphasis to the investigation of CO2 solubility at equilibrium state. In order to investigate the effect of promoter addition, the concentration of APDA has been gradually increased from 0.02 w to 0.10 w in the mixed solvent blend. The generated solubility data are correlated using two different modeling approaches viz., equilibrium based modified form of Kent-Eisenberg (KE) thermodynamic model and feed-forward neural network model. The model prediction is further extended to estimate pH and the overall speciation profile of all the molecular as well as ionic species prevailing in the solvent system. The CO2 solubility data are also analyzed in view of estimating the heat duty requirement for the absorption process. The heat of absorption of CO2 in aqueous (APDA + 1DMAP) blend has been calculated using the Gibbs-Helmholtz equation. Along with solubility measurement, important thermophysical properties such as density and viscosity of the aqueous amine solution are also measured and correlated using established Redlich-Kister and Grunberg Nissan models.